Keratinocytes differentiation and wound healing in rats with streptozotocin – induced diabetes and severe hyperglycemia - Evgeniy V. Ivanov (Endocrinology Research Centre, 2020)
BACKGROUND: Diabetes mellitus leads to disruption of the skin repair processes, but the leading mechanisms of this pathology have not yet been identified. In this regard, in our work, we decided to check how hyperglycaemia affects the process of keratinocyte phenotype changes during wound healing. AIMS: To study the effect of hyperglycaemia on wound healing and differentiation of keratinocytes in a rat streptozotocin-induced diabetes model. MATERIALS AND METHODS: Diabetes mellitus was induced in rats by using streptozotocin, 65 mg / kg, intraperitoneally, once. The wound was applied in the supra-scapular region on the 42nd day, after which (after 8, 16, and 24 days) the repair process was evaluated using histological methods. Immunohistochemistry was used to evaluate the expression of cytokeratin-10 and cytokeratin-17. RESULTS: In rats with diabetes mellitus, wound healing slowed down in the later stages, compared with the control group. In general, wound healing was accompanied by an increase in the expression of cytokeratin-10 in its region compared with intact skin, and contractile keratinocytes activation was disrupted in diabetic rat wounds. CONCLUSIONS: Hyperglycaemia slightly slows wound healing in rats and impairs contractile keratinocytes activation.